Interest rate rules under financial dominance - Vivien Lewis; Markus Roth (Deutsche Bundesbank, 2018)
We study the equilibrium properties of a business cycle model with financial frictions and price adjustment costs. Capital-constrained entrepreneurs finance risky projects by borrowing from banks. Banks, in turn, make loans using equity and deposits. Because financial contracts are not contingent on aggregate risk, bank balance sheets are hit when entrepreneurial defaults are higher than expected. Macroprudential policy imposes a positive response of the bank capital ratio to lending. Our main result is that the Taylor Principle is violated when this response is too weak. Then macroprudential policy is ineffective in stabilizing debt and monetary policy is subject to 'financial dominance'. A too aggressive response of the interest rate to inflation can lead to debt disinflation dynamics that destabilize the financial sector.
Keywords: E32; E44; E52; E58; E61; 330; bank capital; financial dominance; interest rate rule; macroprudential policy; Taylor Principle